The quintenary influence of industrial wastes on the compressive strength of high-strength geopolymer concrete under different curing regimes for sustainable structures; a GSVR-XGBoost hybrid model - Garcia, Cesar; Andrade Valle, Alexis Ivan; Hashim Muhodir, Sabih; Onyelowe, Kennedy C.; Imran, Hamza; Henedy, Sadiq N.; Chilakala, Bala Mahesh; Verma, Manvendra (Frontiers in Built Environment, 2024)
The production of geopolymer concrete (GPC) with the addition of industrial wastes as the formulation base is of interest to sustainable built environment. However, repeated experimental trials costs a huge budget, hence the prediction and validation of the strength behavior of the GPC mixed with some selected industrial wastes. Data gathering and analysis of a total 249 globally representative datasets of a high-strength geopolymer concrete (HSGPC) collected from experimental mix entries has been used in this research work. These mixes comprised of industrial wastes; fly ash (FA) and metallurgical slag (MS) and mix entry parameters like rest period (RP), curing temperature (CT), alkali ratio (AR), which stands for NaOH/Na2SiO3 ratio, superplasticizer (SP), extra water added (EWA), which was needed to complete hydration reaction, alkali molarity (M), alkali activator/binder ratio (A/B), coarse aggregate (CAgg), and fine aggregate (FAgg). These parameters were deployed as the inputs to the modeling of the compressive strength (CS). The range of CS considered in this global database was between 18 MPa and 89.6 MPa. The FA was applied between 254.54 kg/m3 and 515 kg/m3 while the MS was applied between 0% and 100% by weight of the FA to produce the tested HSGPC mixes. The Gaussian support vector regression hybridized with the extreme gradient boosting algorithms (GSVR-XGB) has been deployed to execute a prediction model for the studied concrete CS. The basic linear fittings to determine agreement between the parameters and the Pearson correlation between the studied parameters of the geopolymer concrete were presented. It can be observed that the CS showed very poor correlations with the values of the input parameters and required an improvement of the internal consistency of the dataset to achieve a good model performance. This necessitated the deployment of the super-hybrid interface between the Gaussian support vector regression (GSVR) and the extreme gradient boosting (XGB) algorithms. The frequency histogram and the Gaussian support vector machine architecture for the output (CS) are presented and these show serious outliers in the support vector machine which were tuned by using the boosting algorithms combined in the computation interface to enhance the GSVR hyperplane. This eventually produced a super-performance and execution speed remarkable for its use in the forecasting of the CS of the high-strength geopolymer concrete (HSGPC) for sustainable concrete design, production and placement during construction activities. Furthermore, the measure of the performance evaluation in comparison between measured and predicted values are presented on the basis of the MAE, MSE, RMSE, MAPE and R2 for the MLR and the SVR. It can be observed that the MAE produced 16.731 MPa, MSE produced 173.398 MPa, RMSE produced 0.452 MPa, MAPE produced 0.486 MPa and with R2 of 0.720 for the MLR and the MAE produced 6.855 MPa, MSE produced 109.582 MPa, RMSE produced 10.468 MPa, MAPE produced 0.190 MPa and with R2 of 0.994. These results show the super-performance display of the hybrid algorithms of the Gaussian support vector regression (GSVR) and the extreme gradient boosting (XGBoosting), which produced a superior and decisive model with excellent output compared to the MLR. Also, the execution time reduced from a 24-hour runtime to 1-hour runtime, which reduced the time and energy utilized in the model execution. Also, the GSVR-XGB produced minimal errors. The significant parameters that have a substantial effect on the outcome can be identified as AR and SP for the MLR and the GSVR-XGB, respectively and this presents insights into the behavior of geopolymer concrete.